Clastogenicity of landfarming soil treated with sugar cane vinasse - Da Silva Souza, Tatiana; Hencklein, Fabiana Aparecida [UNESP]; De Franceschi de Angelis, Dejanira [UNESP]; Fontanetti, Carmem Silvia [UNESP] (Springer Nature, 2013)
The addition of nutrients and/or soil bulking agents is used in bioremediation to increase microbial activity in contaminated soils. For this purpose, some studies have assessed the effectiveness of vinasse in the bioremediation of soils contaminated with petroleum waste. The present study was aimed at investigating the clastogenic/aneugenic potential of landfarming soil from a petroleum refinery before and after addition of sugar cane vinasse using the Allium cepa bioassay. Our results show that the addition of sugar cane vinasse to landfarming soil potentiates the clastogenic effects of the latter probably due the release of metals that were previously adsorbed into the organic matter. These metals may have interacted synergistically with petroleum hydrocarbons present in the landfarming soil treated with sugar cane vinasse. We recommend further tests to monitor the effects of sugar cane vinasse on soils contaminated with organic wastes. © 2012 Springer Science+Business Media B.V.
Keywords: Allium cepa; Bioremediation; Chromosome aberrations; Chromosome breakages; Chromosome aberration; Clastogenicity; Contaminated soils; Microbial activities; Organic wastes; Petroleum hydrocarbons; Petroleum wastes; Activation analysis; Bioassay; Biotechnology; Chromosomes; Petroleum chemistry; Soil pollution; Sugar cane; Soils; petroleum; fertilizer; mutagenic agent; bioassay; bioremediation; contaminated land; microbial activity; petroleum hydrocarbon; soil remediation; sugar cane; agricultural land; chromosome breakage; concentration (parameters); controlled study; farming system; mutagen testing; nonhuman; onion; organic waste; petrochemical industry; physical chemistry; pollution monitoring; soil management; soil pollutant; soil quality; sugarcane; vinasse; agriculture; chemistry; ecosystem restoration; evaluation; industrial waste; methodology; oil spill; soil; Saccharum; Agriculture; Biodegradation, Environmental; Biological Assay; Environmental Remediation; Fertilizers; Industrial Waste; Mutagens; Onions; Petroleum; Petroleum Pollution; Soil; Soil Pollutants